Physical punishment and the development of personality traits a case for guidance intervention - Benson, Mercy S.; Chi, Cleofe L.; Ganaden, Mildred S.; De Guzman, Ligaya S.; Soria, Robinson C. (2006)
This study was built on the theoretical framework that unwanted behavior of youngsters can be corrected with the use of better and healthier alternatives that will leave them a lasting positive effect and develop them for their adult life with balanced personalities. The quantitative method was used for finding individual participants' personalities in terms of the eight aspects from the POI. The qualitative method was also used in discussing the data gathered for the respondents in the eight case studies. It was found that punished individuals tend to be stubborn, rebellious, hard to deal with, and possess fear toward authority figures. A guidance program that consists of activities that will contribute to the rehabilitation of physically punished individuals was proposed to answer their needs based on the results of the study.
Thesis (M.A. Guidance)--University of the Philippines, Diliman.
Keywords: Corporal punishment -- Philippines; School discipline -- Philippines; Personality development -- Philippines